Reversion of Severe Mitral Insufficiency in Peripartum Cardiomyopathy Using Levosimendan (2015)
Idiopathic peripartum cardiomyopathy presenting with heart failure is a true diagnostic and treatment challenge. Goal oriented clinical management aims at the relapse of left ventricular systolic dysfunction. A 35-year-old patient on her 12th day post-delivery presents progressive signs of heart failure. Transthoracic echocardiography showed severe mitral insufficiency, mild left ventricular dysfunction, mild tricuspid insufficiency, severe pulmonary hypertension, and right atrial enlargement. With wet and cold heart failure signs, the patient was a candidate for inodilator cardiovascular support and volume depletion therapy. As the patient presented a persistent tachycardia at rest, levosimendan was chosen over dobutamine. Levosimendan was administered at a dose of 0.2 g/kg/min during a period of 24 hours. After inodilator therapy, the patient's signs and symptoms of heart failure began to decrease, showing improvement of dyspnea, mitral murmur grade went from IV/IV to II/IV, filling pressures and systemic and pulmonary resistance indexes decreased, arterial blood gases improved, and an echocardiography performed 72 h later showed non-dilated cardiomyopathy, mild cardiac contractile dysfunction, mild mitral insufficiency, type I diastolic dysfunction and improvement of pulmonary hypertension. Cardiovascular function in peripartum cardiomyopathy tends to go back to normality in 23-41% of the cases, but in a large group of patients, severe ventricle dysfunction remains months after initial symptoms. This article describes the diagnostic process of a patient with peripartum cardiomyopathy and a successful reversion of a severe case of mitral insufficiency using levosimendan as a new therapeutic strategy in this clinical context.